Analisis Kepuasan-Kepentingan Pengguna Terhadap Sistem Informasi Perpustakaan Universitas Muhammadiyah Riau - Noprianto, Eko (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Information systems are an important component in library management, so that they can maximize the services offered to users. However, in practice, the implementation of information systems will not be separated from problems that become obstacles in their use. This research aims to evaluate the implementation of the UMRI library information system based on the level of user satisfaction and interests. The method used is descriptive quantitative with the PIECES framework approach. The research population was active UMRI students who were registered as library members, with a sample size of 100 students. Research data was collected using questionnaires, and data analysis applied the importance-performance analysis (IPA) method. The research results show that the level of user satisfaction is in the quite satisfied category, with an average value of 3.14. The level of user interest is also in the quite satisfied category, with an average value of 3.18. Based on IPA analysis, the level of conformity between user satisfaction and interests is 98.78%, which means that the quality of UMRI library information system services is not in accordance with user needs. The two indicators that are the main priority for improvement are performance and service.